2017
DOI: 10.1002/cpt.577
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Complex Pharmacokinetics for Daratumumab Dose Regimen in Patients With Relapsed/Refractory Multiple Myeloma

Abstract: New therapeutic strategies are urgently needed to improve clinical outcomes in patients with multiple myeloma (MM). Daratumumab is a first‐in‐class, CD38 human immunoglobulin G1κ monoclonal antibody approved for treatment of relapsed or refractory MM. Identification of an appropriate dose regimen for daratumumab is challenging due to its target‐mediated drug disposition, leading to time‐ and concentration‐dependent pharmacokinetics. We describe a thorough evaluation of the recommended dose regimen for daratumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 7 publications
8
68
0
Order By: Relevance
“…According to this model, daratumumab plasma concentrations of 236 µg/mL are necessary to achieve 99% CD38 saturation in vivo. [13][14][15] Performing the cell line saturation assay with dilutions of patient plasma, we determined a daratumumab concentration of 11.5 µg/mL in our patient six weeks after the last infusion, when pre-existing and newly generated myeloma cells showed full CD38 saturation with antibody. This concentration was expected based on pharmacokinetic data from the clinical trials (peak levels, half-life, targetmediated clearance), 4 but clearly challenged the target saturation model.…”
Section: -9mentioning
confidence: 99%
“…According to this model, daratumumab plasma concentrations of 236 µg/mL are necessary to achieve 99% CD38 saturation in vivo. [13][14][15] Performing the cell line saturation assay with dilutions of patient plasma, we determined a daratumumab concentration of 11.5 µg/mL in our patient six weeks after the last infusion, when pre-existing and newly generated myeloma cells showed full CD38 saturation with antibody. This concentration was expected based on pharmacokinetic data from the clinical trials (peak levels, half-life, targetmediated clearance), 4 but clearly challenged the target saturation model.…”
Section: -9mentioning
confidence: 99%
“…In our article, we reported that daratumumab exhibited time‐dependent and concentration‐dependent pharmacokinetics (PK) consistent with target‐mediated drug disposition, based on data from studies of daratumumab as a monotherapy 1. Jacobs and Mould2 posit that saturation of the neonatal Fc‐receptor (FcRn) contributes to the nonlinear PK of daratumumab.…”
mentioning
confidence: 94%
“…This approximation is frequently made to describe the pharmacokinetics of mAbs in case of nonlinear shape of terminal elimination and has been used for 23 therapeutic antibodies in 28 studies (table 1). In the 18 studies where "full" Michaelis-Menten model is used [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] , VM and KM values are highly variable between studies, VM and KM ranges being 0.008-26.4 mg/day and 0.02-33.9 mg/L, respectively. However, the Michaelis-Menten term has been used in simplified forms.…”
Section: Michaelis-menten Modelmentioning
confidence: 99%